2019
DOI: 10.1111/imr.12827
|View full text |Cite
|
Sign up to set email alerts
|

Advances in genetics toward identifying pathogenic cell states of rheumatoid arthritis

Abstract: Summary Rheumatoid arthritis (RA) risk has a large genetic component (~60%) that is still not fully understood. This has hampered the design of effective treatments that could promise lifelong remission. RA is a polygenic disease with 106 known genome‐wide significant associated loci and thousands of small effect causal variants. Our current understanding of RA risk has suggested cell‐type‐specific contexts for causal variants, implicating CD4 + effector memory T cells, as well as monocytes, B cells and stroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…The studies showed that the development of RA is based on heredity and epigenetics, but environmental factors also play an important role, such as cigarette smoke and dust contact, especially the microbiome representing the "internal" environment ( Figure 1) (Amariuta et al, 2020;Scherer et al, 2020). And the susceptibility of RA is related to environmental factors, such as smoking and infection, which may be mediated by gut microbiome (Klareskog et al, 2006;Luckey et al, 2013).…”
Section: Gut Microbiome In the Etiology Of Rheumatoid Arthritismentioning
confidence: 99%
“…The studies showed that the development of RA is based on heredity and epigenetics, but environmental factors also play an important role, such as cigarette smoke and dust contact, especially the microbiome representing the "internal" environment ( Figure 1) (Amariuta et al, 2020;Scherer et al, 2020). And the susceptibility of RA is related to environmental factors, such as smoking and infection, which may be mediated by gut microbiome (Klareskog et al, 2006;Luckey et al, 2013).…”
Section: Gut Microbiome In the Etiology Of Rheumatoid Arthritismentioning
confidence: 99%
“…To date, over 100 genetic loci have been associated with RA [ 28 ]. The pathogenesis of RA has a polygenic basis, where 50% of disease risk is thought to be genetic and one-third of this risk is attributable to the HLA region [ 17 ].…”
Section: Genetics In Rheumatoid Arthritismentioning
confidence: 99%
“…Thus, genetic variation can also be explained by RA risk alleles in non-HLA loci. In early GWAS, peptidyl arginine deiminase 4 ( PADI4 ), protein tyrosine phosphatase non-receptor type 22 ( PTPN22 ), and cytotoxic T-lymphocyte-associated protein 4 ( CTLA4 ) genes were identified as initial non-HLA RA risk loci [ 29 , 30 ] ( Figure 2 ), with these findings being subsequently replicated in multiple cohorts in the following years [ 28 ]. There has been an exponential increase in the number of genes associated with RA since 2007, as several collaborative efforts have led to the development of international consortia [ 31 ].…”
Section: Genetics In Rheumatoid Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…It is recognized that gene polymorphisms have been involved in these disorders pathogenesis (3,4). To date, at least 88 genomic regions have been identified associated with SLE susceptibility, such as TNFSF4, STAT4, and TNIP1, and about 106 susceptible genes were reported to associate with RA, such as CD28, IL3-CSF2, NFKBIE (5,6). However, finding out more risk polymorphisms for RA and SLE will be helpful to better elucidate the pathogenesis of these diseases.…”
Section: Introductionmentioning
confidence: 99%